The Concept of Tasbīḥ Al- Ālam (Universe’s Glorification): A Comparative Study of Fakhr al-Dīn al-Rāzī’s and Ibn ‘Arabī’s Interpretations - Inarotul Aini (Universitas Islam Negeri Mataram, 2017)
In the Islamic doctrine, Allah is the creator, while the universe including human beings is the creatures. The universe glorifies Allah. Glorification is the proof of the universe’s obedience to Allah. The study aims to shed light on how the universe performs such a glorification. This article examines the concept of tasbīḥ al-‘ālam proposed by Muḥammad bin al-Ḥusayn Fakhr al-Dīn al-Rāzī (544 H/1149 AD – 606 H/1209 AD), a rationalist, in his book Tafsīr al-Kabīr aw Mafātiḥ al-Ghayb and compares it with that of Muhyiddin Ibn ‘Arabī ( 560 H/ 1149 AD), a mystical interpreter, in his book Tafsīr al-Qur’ān al-Karīm. This study shows that there are distinct processes and ways of how the universe commends to God. According to Ibn Arabī, the commendation by the universe is the process of getting annihilation and the unifiction of existence (waḥdah al-wujūd); while al-Rāzī clarifies that the process itself is in metaphoric meaning (majāzi) contingent upon the condition of each part of the universe.